When Extrinsic Rewards Become "Sour Grapes": An Experimental Study of Adjustments in Intrinsic and Prosocial Motivation. (December 2019) - Kroll, Alexander; Porumbescu, Gregory A.
This article challenges conventional wisdom put forward by the motivational crowding literature by examining whether hypothetical changes to incentive structures can cause variation in employee motivation. It links such motivational adjustments to theories of cognitive dissonance and self-rationalization, and thereby offers a more nuanced perspective on government reforms in the area of human resource management. The article puts forward the idea that expectations of few extrinsic rewards can raise employees' levels of intrinsic and prosocial motivation; this response is seen as a cognitive coping mechanism to self-justify the value of one's work. A randomized experiment with 129 public administration students provides partial evidence for the hypothesized effect. Students who were confronted with media information suggesting that few extrinsic rewards can be expected in a public-sector career reported higher scores of intrinsic motivation than the group whose vignette suggested the opposite. No effect was found with regard to students' public service motivation.